1994
DOI: 10.2105/ajph.84.4.646
|View full text |Cite
|
Sign up to set email alerts
|

Occupational injury deaths of 16- and 17-year-olds in the United States.

Abstract: Data from the National Traumatic Occupational Fatalities surveillance system were used to analyze occupational injury deaths of civilian 16- and 17-year-olds during 1980 through 1989. There were 670 deaths; the rate was 5.11 per 100,000 full-time equivalent workers. The leading causes of death were incidents involving motor vehicles and machines, electrocution, and homicide. Workers 16 and 17 years old appear to be at greater risk than adults for occupational death by electrocution, suffocation, drowning, pois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 10 publications
1
63
0
Order By: Relevance
“…A previous analysis of our cohort found that rates for fatal occupational injury were greatest among workers aged <25 years and >45 years and that mortality was highest in the 1st year of employment(l0). In the United States, workers aged 16 and 17 years were at greater risk of death from occupational injury than older workers were (18). It is very difficult to separate out the effect of youth and inexperience as age is highly correlated with work experience.…”
Section: Discussionmentioning
confidence: 99%
“…A previous analysis of our cohort found that rates for fatal occupational injury were greatest among workers aged <25 years and >45 years and that mortality was highest in the 1st year of employment(l0). In the United States, workers aged 16 and 17 years were at greater risk of death from occupational injury than older workers were (18). It is very difficult to separate out the effect of youth and inexperience as age is highly correlated with work experience.…”
Section: Discussionmentioning
confidence: 99%
“…[5,16] Accidents among adolescent workers are common, and their fatality is greater. [17] Absoud and Harrop [18] analyzed 73 patients and found that the underlying cause of the accident was inadequate knowledge of the machine they were operating in 14%. Considering that age and experience are closely related, they should be evaluated together.…”
Section: Discussionmentioning
confidence: 99%
“…Further, back pain in particular is of concern in adolescence, and may place these young workers at greater risk for future musculoskeletal problems. Risks of severe and even fatal injuries occur most frequently among boys rather than girls, 2,3,5,6,10,18 indicating different types of employment activities and possibly job demands. 6,18 In this study, data regarding fatal injuries were not collected.…”
Section: Discussionmentioning
confidence: 99%
“…In this situation there was a need of 384 participants in each town, totalizing 768 students. In a previous survey conducted in both towns, it was 3 FM et al observed that selecting 50% of the students in each classroom, and each school (total of 4 schools), and using a stratified random sample as mentioned above, the sample size would be 862 students. This would allow losses up to 12%.…”
Section: Methodsmentioning
confidence: 99%